2014
DOI: 10.1116/1.4897170
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and mechanical properties of amorphous coatings in the Ti-B-Si-Al-N system grown by cathodic arc evaporation from TiB2, Ti33Al67, and Ti85Si15 cathodes

Abstract: Ti-B-Si-Al-N coatings were grown on cemented carbide substrates in an industrial scale cathodic arc evaporation system using Ti 33 Al 67 , Ti 85 Si 15 , and TiB 2 cathodes in a reactive N 2 atmosphere. The microstructure of the as-deposited coatings changes from nanocrystalline to amorphous with addition of (B+Si+Al), or high amounts of (B+Si) to TiN. In the as-deposited state, the 4 µm-thick amorphous coatings are dense and homogenous, besides slight compositional modulation with Ti-rich layers induced by rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The more possible reason is a low density of the short range ordered species (bonds) with high strength. In earlier works, the hardness of the amorphous TiAlBSiN coatings was reported to be~15 GPa [81], 21 GPa [80] and 17.1 ± 0.5 GPa [21] and the growth of hardness was observed for coatings reported in [21] and [81] up to 21 GPa after annealing at 700°C and up to~20 GPa after annealing at 800°C, respectively, but the hardness decreased for higher annealing temperatures [80].…”
Section: Nanoindentation Testsmentioning
confidence: 86%
See 1 more Smart Citation
“…The more possible reason is a low density of the short range ordered species (bonds) with high strength. In earlier works, the hardness of the amorphous TiAlBSiN coatings was reported to be~15 GPa [81], 21 GPa [80] and 17.1 ± 0.5 GPa [21] and the growth of hardness was observed for coatings reported in [21] and [81] up to 21 GPa after annealing at 700°C and up to~20 GPa after annealing at 800°C, respectively, but the hardness decreased for higher annealing temperatures [80].…”
Section: Nanoindentation Testsmentioning
confidence: 86%
“…Following this idea, oxidation resistance of the coatings strongly depends on the thermal stability of its amorphous structure and the interdiffusion of the elements in both coating and substrate. The effect of substrate elements diffusing into the protective coating structure was reported in many papers [21][22][23][24]. It was shown that the crystallization starts directly at the coating/substrate interface due to the diffusion of substrate elements into the coating layer [23,24].…”
Section: Introductionmentioning
confidence: 94%
“…12 These routes remain to be confirmed, although a stable arc process has been reported for the use of a TiB 2 cathode in N 2 for synthesis of nitride multielement alloys. 13 In this letter, we have explored conditions allowing the stable vacuum arc plasma generation from a TiB 2 cathode. The erosion of the cathode surface is correlated to charge-state-resolved plasma analysis of ion chemistry and ion energy, macroparticle generation, as well as resulting film composition.…”
mentioning
confidence: 99%
“…We have chosen the Ti-Si-B-N system for exploring amorphous nitrides, first grown by arc-deposition [11]. Here, we report the growth and properties of amorphous (TiB2) 1−x Si x N thin films deposited using a hybrid powering setup, where the Si target is operated in a conventional DCMS mode and the TiB2 target is operated in HIPIMS [12] mode.…”
Section: Introductionmentioning
confidence: 99%